Banker to the poor micro-lending and the battle against world poverty - Yunus, Muhammad 1940- (PublicAffairs, 2007)
The founder of the Grameen Bank relates how he developed the system of micro-credit to help eradicate poverty in countries such as Bangladesh by providing financial education and small loans to rural families.